2017
DOI: 10.1038/srep42840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-146a on the osteogenesis of adipose-derived mesenchymal stem cells and bone regeneration

Abstract: Increasing evidence has indicated that bone morphogenetic protein 2 (BMP2) coordinates with microRNAs (miRNAs) to form intracellular networks regulating mesenchymal stem cells (MSCs) osteogenesis. This study aimed to identify specific miRNAs in rat adipose-derived mesenchymal stem cells (ADSCs) during BMP2-induced osteogenesis, we selected the most significantly down-regulated miRNA, miR-146a, to systematically investigate its role in regulating osteogenesis and bone regeneration. Overexpressing miR-146a notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 59 publications
4
67
0
Order By: Relevance
“…Second, we investigated how miR‐146a contributed to OB and OC. Previous studies showed that the miR‐146a can regulate the OC differentiation through its target gene TRAF6 and inhibit OB differentiation by SMAD4 . Our study reveals that miR‐146a plays roles in accelerating apoptosis, suppressing proliferation and differentiation of both OB and OC.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Second, we investigated how miR‐146a contributed to OB and OC. Previous studies showed that the miR‐146a can regulate the OC differentiation through its target gene TRAF6 and inhibit OB differentiation by SMAD4 . Our study reveals that miR‐146a plays roles in accelerating apoptosis, suppressing proliferation and differentiation of both OB and OC.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies showed that the miR-146a can regulate the OC differentiation through its target gene TRAF6 and inhibit OB differentiation by SMAD4. (22,38) Our study reveals that miR-146a plays roles in accelerating apoptosis, suppressing proliferation and differentiation of both OB and OC. Although the bone mass of miR-146a −/− mice did not differ from that of WT mice, the bone turnover of the former was stronger than that of the latter.…”
Section: Discussionmentioning
confidence: 78%
“…IRAK1 is a serine/threonine kinase whose activity is strongly increased following TLR stimulation and plays a critical role in NFκB signaling by phosphorylating TRAF6 . In addition to its role in immune regulation, miR‐146a has multiple other functions including a role in the osteogenic differentiation of MSCs . Treatment of human AD‐MSCs with TNF‐α, PGN (TLR2 agonist), and LPS enhanced their osteogenic potential, which was associated with NFκB and ERK activation .…”
Section: Micro‐rnas As Novel Modulators Of Tlr‐mediated Response In Mscsmentioning
confidence: 99%
“…[107] Many distinct scaffold types have been tuned to serve the purpose of miRNA delivery, including several hydrogels, [58,92,106,[108][109][110][111][112][113][114] electrospun fibers, [63,[115][116][117][118] and more prolifically porous or spongy scaffolds. [46,47,50,54,55,96,112,[119][120][121][122][123][124][125][126][127][128][129][130] Before reviewing the details of their applications, summarized in Table 2 and described further in the next section, we will discuss the key characteristics making these materials amenable to miRNA delivery. First very general qualities must be fulfilled: biocompatibility, bioresorbability and ease of fabrication.…”
Section: Scaffolds For Microrna Deliverymentioning
confidence: 99%
“…miR-2861 has been shown to be increase the osteogenic commitment of human periodontal ligament stem cells (hPDLSCs) grown on a 3D scaffold and demonstrated the successful overexpression of miR-2861 and RUNX2 in hPDLSCs cultured in presence of the scaffold under osteogenic and standard conditions. [126] Xie et al [127] showed that miR-146a negatively regulates osteogenesis and bone regeneration of ASCs both in vitro and in vivo. Overexpressing miR-146a using lentivirus suppressed ASC osteogenesis while inhibition of miR-146a greatly promoted this process in vitro, corresponding with modulation of miR-146a's direct target, SMAD4, an important coactivator in the BMP signaling pathway.…”
Section: Osteogenesis and Bone Repairmentioning
confidence: 99%